Pemanfaatan Media Sederhana dalam Pembelajaran Fisika untuk Materi Udara bagi Kelompok Anak di Sentani - Radjabaycolle, Flinn C.; Bunga, Martina; Susilowati, Rachmadani O. (LPPM Uncen, 2025)
Physics is often perceived as one of the most difficult subjects, leading to a lack of interest, particularly among students. This issue is exacerbated by the reliance on rote memorization of formulas and definitions, rather than a deep understanding of the concepts. Such an approach hinders students' ability to think critically and creatively, which is essential for problem-solving in real-world applications. This community service program aimed to address these challenges by providing primary school children in Sentani, Jayapura, with engaging, hands-on experiments to better understand basic physical concepts, specifically the properties of air. The activities included simple experiments such as